Coast Guard Polar Icebreaker Modernization: Background, Issues, and Options for Congress - O'Rourke, Ronald (2009)
Of the Coast Guard's three polar icebreakers, two-Polar Star and Polar Sea-have exceeded their intended 30-year service lives. The Polar Star is not operational and has been in caretaker status since July 1, 2006. A 2007 report from the National Research Council (NRC) on the U.S. polar icebreaking fleet states that "U.S. [polar] icebreaking capability is now at risk of being unable to support national interests in the north and the south" On July 16, 2008, Admiral Thad Allen, the Commandant of the Coast Guard, testified that: "Today, our nation is at a crossroads with Coast Guard domestic and international icebreaking capabilities. We have important decisions to make. And I believe we must address our icebreaking needs now. " The Coast Guard is studying how many polar icebreakers, with what capabilities, should be procured as replacements for Polar Star and Polar Sea. Under the Coast Guard's current schedule, the first replacement polar icebreaker might enter service in 8 to 10 years, by which time Polar Star and Polar Sea could be about 40 years old. The Coast Guard estimated in February 2008 that new replacement ships might cost $800 million to $925 million each in 2008 dollars, and that the alternative of extending the service lives of Polar Sea and Polar Star for 25 years might cost about $400 million per ship. CRS Report for Congress